The Impact of Social Safety Net Programs on Poor Household Income - Prayitno, Hengky S.H.; Santoso, Dwi Budi; Ekawaty, Marlina (Universitas Negeri Semarang, 2018)
Indonesian government has established social safety net programs to reduce poverty and increase the productivity and income of poor households. Among other provinces in Indonesia, East Java has the highest poverty rate. Thus, this research aims to analyze the effectiveness of social safety net programs in reducing poverty rate in East Java. This research uses quantitative approach to measure the contribution of social safety net programs towards the income of poor households in East Java. This research employs equivalent simultaneous equation with three-stage least square (3SLS) method on secondary cross section data obtained from National Socio-Economic Survey (Susenas), March 2015. This research calculates and analyzes the impacts of social aid, social protection and labor market intervention programs towards the income of poor household income. The results show that social aid and labor market intervention programs have positive implication on the income of poor households. On the other hand, social security has no significant implication. Moreover, social security provides a safety net when a household faces unexpected situation such as redundancy, accident and death. Social security programs prevent poor households for being poorer.